Effects of protein environment on the site energy of cofactors in the reaction center from photosynthetic purple bacterium thermochromatium tepidum - Huang, Junye (2015)
Despite intensive research efforts, the detailed mechanism of charge separation and energy transfer in the reaction center of photosynthetic systems remain unclear. Unidirectionality of charge separation in the two quasisymmetric cofactor branches is one of the most puzzling fact in the charge separation process. To find out the origin of unidirectionality of charge separation in reaction centers, this work investigates the effect of protein environment on the site energy of cofactors by using a hybrid Quantum Mechanics/Molecular Mechanics calculation method and atomic coordinates trajectories from molecular dynamics simulation of reaction center complex of photosynthetic purple bacterium Thermochromatium tepidum. The effects of protein environment on site energy of cofactors were confirmed in the calculations. Most of the cofactors increase its site energy in various extents with the consideration of point charges. In the protein environment, cofactors PL, PM, BPheL and BPheM increase in site energies of 0.047, 0.104, 0.034, and 0.087 eV, respectively. In addition, protein residues with different electronic properties were found to have different effects on site energies. Charged and non-polar residues were found to increase the site energy value, while polar residues reduce the site energy. Histidine residues, especially the ones that are ligated with the Mg ions at the center of bacteriochlorophylls, were successfully pinpointed as the major sources of the increment effects in the protein environment. Most remarkable effects were observed on PL (increases 0.024 eV) and PM (increases 0.040 eV). All His residues within 20 ̊A of the cofactors collectively contribute to 117% and 66% of the site energy changes on PL and PM respectively. In addition to His residues, this research also suggests that another contribution to unidirectionality of charge separation in reaction center is the difference of protein environment around cofactor PM, possibly CRT molecule, which is responsible for about 0.035 eV of increment effect on site energy.